Aufbruch: Ein Weg in die Philosophie - Joisten, Karen (Verlag Karl Alber, 2023)
The second revised edition of ‘Aufbruch. Ein Weg in die Philosophie’ traces the inseparable connection between the adventure of philosophical thinking and the perpetually twofold nature of man. This book demonstrates that philosophising corresponds to basic human attitudes and can be a path for every person who is creatively on a journey to themselves. ‘Aufbruch’ delineates the open and inherently contentious double structure that essentially characterises human beings in vivid descriptions of phenomena. This can be demonstrated, among other things, through the attitudes of living and walking and of stumbling, tearing down and resisting.